2021
DOI: 10.3390/pathogens10030281
|View full text |Cite
|
Sign up to set email alerts
|

The Brilliance of Borrelia: Mechanisms of Host Immune Evasion by Lyme Disease-Causing Spirochetes

Abstract: Lyme disease (LD) has become the most common vector-borne illness in the northern hemisphere. The causative agent, Borrelia burgdorferi sensu lato, is capable of establishing a persistent infection within the host. This is despite the activation of both the innate and adaptive immune responses. B. burgdorferi utilizes several immune evasion tactics ranging from the regulation of surface proteins, tick saliva, antimicrobial peptide resistance, and the disabling of the germinal center. This review aims to cover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 132 publications
0
32
0
Order By: Relevance
“…They can persistently infect and survive in their reservoir hosts for prolonged periods of time without causing any signs of a disease in the infected animals. In fact, spirochetes developed numerous strategies to overcome the innate and the adaptive immune response to prevent elimination by the host’s immune system (Hyde 2017 ; Kurokawa et al 2020 ; Lin et al 2020 ; Anderson and Brissette 2021 ). The ~1780 genes in the genome of B. burgdorferi s.s. strain B31 M1 are located on a single linear chromosome (910 kbp) and ~21 linear and circular plasmids (Fraser et al 1997 ; Casjens et al 2000 ; Pal and Fikrig 2003 ; Schwartz et al 2021 ) and can be regulated to respond to environmental changes.…”
Section: Strategies Of B Burgdorferi Sl To Survive In Ticks and Vertebrate Hostsmentioning
confidence: 99%
“…They can persistently infect and survive in their reservoir hosts for prolonged periods of time without causing any signs of a disease in the infected animals. In fact, spirochetes developed numerous strategies to overcome the innate and the adaptive immune response to prevent elimination by the host’s immune system (Hyde 2017 ; Kurokawa et al 2020 ; Lin et al 2020 ; Anderson and Brissette 2021 ). The ~1780 genes in the genome of B. burgdorferi s.s. strain B31 M1 are located on a single linear chromosome (910 kbp) and ~21 linear and circular plasmids (Fraser et al 1997 ; Casjens et al 2000 ; Pal and Fikrig 2003 ; Schwartz et al 2021 ) and can be regulated to respond to environmental changes.…”
Section: Strategies Of B Burgdorferi Sl To Survive In Ticks and Vertebrate Hostsmentioning
confidence: 99%
“…At late EC exposure to Bb, we observed the formation of Bb aggregates, but single motile and viable spirochetes were still present in the culture medium. Past studies have suggested that multiple factors can lead to Bb aggregation (Anderson and Brissette, 2021;Sapi et al, 2012;Alban et al, 2000). However, in our assay we determined that this is the result of the high MOI used, since it also occurs when large amounts of spirochetes are cultured in their normal growth medium (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…Bb can also localize intracellularly in many host cell types, including ECs, from which it can escape clearance and transmigrate transcellularly (Coleman et al, 1995;Tan et al, 2021;Kumar et al, 2015). Moreover, Bb can undergo different morphological transitions, forming for example spherical round bodies and aggregates (Anderson and Brissette, 2021;Sapi et al, 2012). Whether these alternative Bb forms emerge as a result of the harsh in vitro conditions, the multiplicity of infection, or represent a mechanism to evade in vivo host immune responses remains controversial (Murgia and Cinco, 2004;Anderson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Lyme disease has been demonstrated to destroy germinal centers of lymph nodes during early infection [72, 73, 84, 85]. These germinal centers are a vital structure that produces long-lived immunoglobulin responses through T-cell-dependent interactions [86].…”
Section: Discussionmentioning
confidence: 99%